MARKETING MANAGEMENT IN RECREATIONAL ORGANISATIONS - Kantyka, Joanna; Nagody-Mrozowicz, Kazimierz; Ochoa Siguencia, Luis; Pietrakowski, Piotr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of the paper is to analyse selected aspects of marketing activities of recreational organizations from the Silesian Voivodship. The following research problems were diagnosed: analysis of the marketing structure, directions of activity and development as well as the meaning and motives of applying marketing in the surveyed recreational organizations functioning in the Silesian Voivodship. The results of the research presented in this paper and the considerations based on them allow formulating a general conclusion that profit and non-profit organizations operate in the common market of recreational services, both have a similar phase of the organization's life cycle, pursue similar recreational goals, offer similar services and direct them to the same clients, but the nature of ownership and the organizational and legal form determine the marketing concept model in these organizations.